Self-talk: Review and sport-specific model. (January 2016) - Van Raalte, Judy L.; Vincent, Andrew; Brewer, Britton W.
Abstract: Self-talk is a key component of the sport psychology canon. Although self-talk has been widely endorsed by athletes and coaches as a performance enhancement strategy, a comprehensive model of self-talk in sport that might be used to guide systematic research has yet to be developed. This purpose of this paper is to: (a) review theory and research related to self-talk in sport; and (b) present a sport-specific model that builds upon existing theory and research, and addresses key questions related to self-talk. The paper begins with a definition of self-talk, developed with consideration of the discursive nature of inner speech and dual process theories. Extant self-talk models related to self-talk in sport are reviewed and serve as a foundation for a sport-specific model of self-talk. Components of the model (i.e., self-talk, System 1, System 2, behaviour, contextual factors, personal factors) are presented, the reciprocal relationships among model components are explored, and implications of the sport-specific model of self-talk are discussed. Highlights: Self-talk can be defined as syntactically recognizable communication. The sender of a self-talk message is also the intended receiver. Self-talk can be expressed internally or out loud. A sport-specific model of self-talk can be used to guide research and practice. There are multiple and reciprocal relationships among self-talk model factors.